Pengaruh Perawatan Payudara Pada Ibu Hamil Terhadap Peningkatan Produksi Asidi Wilayah Kerja Puskesmas Bonto Marannu - Hariati, Andi (Jurnal Ilmiah Amanah Akademika, 2019)
Breast care is a method to increase the breast milk production. This research is aimed to determine the effect of breast care on increasing milk production in Post-Partum mothers, in Puskesmas Bonto Marannu Tahun 2019. The results showed that 95% of 20 pregnant mother perform breast care with Gymnastics or Massage. Pregnant mother who did breast care milk out as much as 95%. The results of milk production on the first day 10-30 cc/day, there are 8 people (40%) and 20-40 cc/day is also there are as many as 8 people (40%), on the second day of milk production of 40-60 cc/day therewere 10 people (50%), while on the third day of milk production increased to 60-80 cc/day, as many as 15 people (75%). The results also showed that pregnant mother who did not care for her breasts, asmany as 15 people (75%) milk production is not smooth and 5 people (25%) milk did not come out. From the results of this study concluded that pregnant mother prefer to do breast care with Gymnastics or Massage on her breasts. Breast Care with Gymnastics or Breast Massage results in more smooth milk production. Pregnant mother who do breast care have a significant effect on increasing milk production.